The influence of secure image, rate and charges, and variation of product towards customer interest in selecting certain banks and the role in net-interest margin in Indonesia - Benny Budiawan Tjandrasa (Universitas Hayam Wuruk Perbanas, 2018)
The purpose of this paper is to prove the influence of the secure image on the interest of customers in selecting certain banks, and to explore the role of the secure image in net interest margin in Indonesia. This research uses a triangular approach which is a combination of a scientific approach and a naturalist approach. The number of questionnaires collected is 300, using simple random sampling, and the hypothesis test uses logistic regression. The results of the research include two things: statistical test result indicates the secure image variable affects the interest of customers in choosing a particular bank; and the exploratory research can explain the role of the secure image variable in Net Interest Margin in Indonesia. The implications of this research are: first, banks and other financial institutions can improve competitiveness by enhancing secure image through enhanced security technology and maintaining the company's reputation in terms of security. Second, the role of the secure image variable in net interest margin can be explained through the application of demand-supply theory. The originality of this research is the verification of the effect of the secure image variable on customer interest in a particular bank and its role in NIM